Issues on Risk Analysis for Critical Infrastructure Protection - Rosato, Vittorio; Di Pietro, Antonio; Rosato, Vittorio; Di Pietro, Antonio (IntechOpen, 2021)
Critical infrastructure provides essential services to citizens. The mutual dependencies of services between systems form a complex 'system of systems' with a large perturbation surface, prone to be damaged by natural and anthropic events. Their intrinsic and extrinsic vulnerabilities could be overcome by providing them adaptive properties to allow fast and effective recovery from loss of functionality. Resilience is thus the key issue, and its enhancement, at the systemic level, is a priority goal to be achieved. This volume reviews recent insights into the different domains (resilience-enhancing strategies, impact and threats knowledge, and dependency-related issues) and proposes new strategies for better critical infrastructure protection.
English
Keywords: Environmental management